Mapping quasi-circular vegetation patch dynamics in the Yellow River Delta, China, between 1994 and 2016 - Lei Shi (Elsevier, 2021)
Because of a decrease in water provision from the Yellow River and the influence of various human actions, the Shandong Yellow River Delta Wetland, selected a Ramsar Wetland of International Importance in 2013, has undergone substantial degradation. Although some restoration work has been undertaken, more adaptive active restoration strategies should be developed based on researches on spontaneous revegetation in this region. In this regard, the quasi-circular vegetation patches (QVPs), characterized by a rapid rate of succession, are thus considered as ideal research targets. The spatial and temporal quantification of QVPs is not only fundamental to determining QVP formation mechanism but also contributes to the development of adaptive restoration strategies for the degraded ecosystems. Therefore, we examined QVP dynamics over seven time periods spanning 22 years using one aerial photograph and seven high-spatial resolution satellite images. We found that although the total number of QVPs remained almost unchanged, the total area had an increasing trend, and that the shape index (SIi=Peremeteri2πAreai) of QVPs tended to initially increase and subsequently decrease, with QVPs finally attaining an almost circular shape. Observations for the period between 2000 and 2016 indicated that the area and shape of QVPs could reach maximum extents within about three years. This knowledge could provide a valuable basis for studying the interactions of QVPs with environment, and the implications/consequences to ecosystems, e.g., mechanisms of the evolution of ecosystems, ecological services etc. We accordingly suggest that developing a long-term remote sensing monitoring and ground-based survey program would make a significant contribution to developing a nature-based solution for the degraded ecosystems in the Yellow River Delta, China.